Badania historyczno-prasowe i ich perspektywy po zmianach ustrojowych w Polsce po roku 1989 (na tle tradycji) = Research into the history of the press, and its perspective on the political changes in Poland after 1989 seen in the context of tradition - Jarowiecki, Jerzy (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Research into the history of the press dates back to the eighteenth century. It was initially undertaken by people involved with the practice of journalism. The press was the subject of research in various disciplines at Polish universities. During the interwar period, the scope of the research was extended, and it was dominated by studies relating to the current needs of education, the practice of journalism and propaganda. A dynamic development in respect of studies of the press occurred after World War II. The Polish Academy of Sciences (PAN) established, as part of its organizational structure, an independent Faculty of the History of the Press in 1952. This was replaced at PAN in 1957 by the Workshop (Pracownia) of the History of Polish Periodicals of the 19 th and 20th centuries, which contributed to multi-directional research and numerous monographic works.The results of historical research into the press were first published in "The Yearbook of the History of Polish periodicals" (from 1962), which was transformed into the "History of the Polish Press Quarterly" in 1975 (until 1993). These magazines were replaced by the "History of the Polish Press Yearbook" (from 1998), published by the Press Studies Commission of the Cracow Branch of PAN. Initially, its research was of a bibliographic character, in line with the Commission`s program. Bibliographic publications appeared, and these became a lasting achievement, as research into the retrospective bibliography of newspapers and into the current bibliography of press studies publications, carried out in the Press Research Centre in Krakow since 1965 (under the editorial supervision of S. Dziki). Researchers in this area of knowledge emphasized the autonomous character of press studies, as well as their interdisciplinary nature. Today, research into the history of the press should acknowledge the importance of the local media, which often express the opinions of the local community and help to integrate these.The history of electronic media, the origins and development of the profession of journalism, and the transformation of the media after 1989, should also be of interest, as well as bibliographic studies, research into freedom of speech, work on media, political and party systems, and studies of religious and social groups.
Keywords: prasa; prasoznawstwo; badania naukowe; przemiany polityczne; Polska Akademia Nauk (PAN); press; press studies; scientific research; political changes; Polish Academy of Sciences